Handbook of financial markets : dynamics and evolution - Hens, Thorsten; Schenk-Hoppe, Klaus Reiner (Handbooks in finance, 2009)
"The models of portfolio selection and asset-price dynamics in this volume seek to explain the market dynamics of asset prices. Presenting a range of analytical, empirical, and numerical techniques as well as several different modeling approaches, the authors depict the state of debate on the market selection hypothesis. By explicitly assuming the heterogeneity of investors, they present models that are descriptive and normative as well, making the volume useful for both finance theorists and financial practitioners."--Jacket